CARACTERISTICAS HEMATOLOGICAS DE LOS NINOS ANORMALES MENTALES - MARTINEZ, LIBORIO (Universidad Nacional Autónoma de Mexico, CD MEXICO, DF, MEX, 1943)
The of Calliphona (Calliphonides) alluaudi* and both sexes of C palmensis* are descr Both spp occur on the Island of Palms, Canary Islands
ANS INST BIOL
Keywords: CARACTERISTICAS, HEMATOLOGICAS, NINOS, MENTALES; CIENCIAS MEDICAS; CIENCIAS CLINICAS; PEDIATRIA